miR-488-5p and its role in melanoma - Arnold, Jessica; Engelmann, Julia C.; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Experimental and Molecular Pathology, 2019)
Due to their ability to regulate dozens to hundreds of target genes simultaneously and, therefore, influence several oncogenic pathways at the same time, microRNAs are a fascinating research object in melanoma. MicroRNAs have been identified as regulators of tumor proliferation, invasion and metastasis in melanoma. More precisely, it has been published that dysregulation of miR-488 contibutes to the progression of several cancer entities. However, the biological functions of miR-488, in special miR-488-5p in melanoma, remain unclear. This study showed the involvement of miR-488-5p in Wnt/β-catenin pathway and the function as a tumor suppressor. Transfection of miR-488-5p mimic led to inhibition of proliferation, migration, anchorage independent growth and led to induction of apoptosis. These data indicated that miR-488-5p acts as a tumor suppressor and is lost during melanoma development. The loss of miR-488-5p was confirmed in vivo by in situ hybridization on melanoma tissue.
EVALuna2:210373